Macroscopic quantum tunneling in a dc SQUID: Instanton splitting - Morais Smith, C. [UNESP]; Ivlev, B.; Blatter, G. (American Physical Society (APS), 1994)
The theory of macroscopic quantum tunneling is applied to a current-biased dc SQUID which constitutes a system of two interacting quantum degrees of freedom coupled to the environment. The decay probability is obtained in the exponential approximation for the overdamped case. Close to the critical driving force of the system, the decay of the metastable state is determined by a unique instanton solution describing the symmetric decay of the phases in each of the two Josephson juctions. Upon reducing the external driving force a new regime is reached where the instanton splits. The doubling of the decay channels reduces the decreasing of the decay rate in the quantum regime. A current-temperature phase diagram is constructed based on the Landau theory of phase transitions. Depending on the external parameters the system develops either a first- or a second-order transition to the split-instanton regime. © 1994 The American Physical Society.